Engineering design, planning, and management - Jack, Hugh (Oxford : Academic Press/Elsevier, 2013)
"This new text covers engineering design methodology with an interdisciplinary approach, concise discussions, and a visual format. Recognizing that design is a process that is most often performed in teams, Jack also covers project management and team dynamic topics where appropriate. The methods in the book are supported with rigor when possible, and are applied to practical situations throughout the book."--Publisher
Keywords: Mechanical engineering; Engineering design